Análisis de los consumos históricos de agua potable en los cantones Latacunga, Guamote y Chunchi - Cazorla Lema, Miguel Angel (2021)
Drinking water system designs have undergone changes over the years due to population growth, since they do not meet the current demand for drinking water required by each canton. The CPE-INEN 005-9-1 establishes endowments that have not received relevant changes in the last years, suggesting to carry out studies of the specific qualities that each sector has, so that they obtain a design adjusted to their reality. For this purpose, data on drinking water consumption were compared throughout the historical record of the Latacunga, Chunchi and Guamote cantons. Additionally, it was analyzed whether during the quarantine period there was an increase in drinking water consumption due to the COVID-19 sanitary emergency, since there could have been a purely residential consumption. This was done by applying statistical processes in Minitab 19. The data analyzed corresponds to the residential area of the aforementioned cantons. Subsequently, the average monthly consumption was defined, and then the analysis of variance ANOVA and Tukey's comparison test were applied in order to determine whether there is a level of statistical significance. Once the results were obtained, the monthly consumption averages are statistically different for each of the cantons. The maximum and minimum consumptions and the months in which high and low consumptions are frequently concentrated for each canton were obtained. In addition, the consumption increase factor Kd was calculated for future inclusion in the design of drinking water systems